2017
DOI: 10.3324/haematol.2016.158485
|View full text |Cite
|
Sign up to set email alerts
|

Targeting the 5T4 oncofetal glycoprotein with an antibody drug conjugate (A1mcMMAF) improves survival in patient-derived xenograft models of acute lymphoblastic leukemia

Abstract: Outcome in childhood acute lymphoblastic leukemia is prognosticated from levels of minimal residual disease after remission induction therapy. Higher levels of minimal residual disease are associated with inferior results even with intensification of therapy, thus suggesting that identification and targeting of minimal residual disease cells could be a therapeutic strategy. Here we identify high expression of 5T4 in subclonal populations of patient-derived xenografts from patients with high, post-induction lev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(15 citation statements)
references
References 47 publications
1
14
0
Order By: Relevance
“…The effectiveness of ADCs depends on numerous factors including tumour expression levels of the target antigen, as well as the ability of tumour cells to internalise and cleave the conjugated drug and undergo apoptosis in response. More recently, it has been demonstrated that this activity can be further enhanced by concurrent administration of other chemotherapeutics [28, 29]. Our study confirms that 5T4 is expressed by all histotypes of EOC, but particularly in women with high-grade serous carcinoma and supports the findings demonstrated in other published series [1113].…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…The effectiveness of ADCs depends on numerous factors including tumour expression levels of the target antigen, as well as the ability of tumour cells to internalise and cleave the conjugated drug and undergo apoptosis in response. More recently, it has been demonstrated that this activity can be further enhanced by concurrent administration of other chemotherapeutics [28, 29]. Our study confirms that 5T4 is expressed by all histotypes of EOC, but particularly in women with high-grade serous carcinoma and supports the findings demonstrated in other published series [1113].…”
Section: Discussionsupporting
confidence: 91%
“…This is consistent with the hypothesis that 5T4 expression may have a functional role in relapse and/or metastasis. Selective elimination of tumour-initiating cells expressing 5T4 using ADCs was shown to be effective at prolonging survival in mouse models of both non small cell lung carcinoma (NSCLC) and pre-B acute lymphoblastic leukemia [2628]. Demonstrating similar effects in EOC, a condition in which most women will relapse following their initial surgery and chemotherapy, could offer additional options for disease control.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The potential of PF-06263507 for the treatment of hematological malignancies was also investigated (66), given the finding that 5T4 was overexpressed on minimal residual acute lymphoblastic leukemia (ALL) cells. PF-06263507 significantly improved survival in mice engrafted with 5T4 + patient-derived ALL cells, and even more so in combination with chemotherapy or dexamethasone.…”
Section: Anti-csc Adcs That Have Been Described In the Literaturementioning
confidence: 99%
“… 63 These viruses were designed to express human 5T4 oncofetal glycoprotein, an N-glycosylated transmembrane protein associated with differentiating embryonic stem cells and tumor-initiating cells of various carcinomas. 68 Dual virus therapy could completely protect mice challenged with B16 tumor cells (which overexpress murine 5T4) when administered as a vaccine, but they were only modestly effective against established tumors. Combining oncolytic adenovirus, MVA and anti-PD-1 antibody resulted in stronger induction of 5T4-specific T-cell responses and significantly increased overall survival.…”
Section: Combination Of Oncolytic Dna Viruses With Pd-1/pd-l1 Checkpomentioning
confidence: 99%